CDK12 inhibition enhances sensitivity of HER2+ breast cancers to HER2-tyrosine kinase inhibitor via suppressing PI3K/AKT. (March 2021) - Li, Hui; Wang, Jinsong; Yi, Zongbi; Li, Chunxiao; Wang, Haijuan; Zhang, Jingyao; Wang, Ting; Nan, Peng; Lin, Feng; Xu, Dongkui; Qian, Haili; Ma, Fei
Abstract: Background: Alhtough anti-HER2 tyrosine kinase inhibitors (TKIs) have radically prolonged survival and improved prognosis in HER2-positive breast cancer patients, resistance to these therapies is a constant obstacle leading to TKIs treatment failure and tumour progression. Methods: To develop new strategies to enhance TKIs efficiency by combining synergistic gene targets, we performed panel library screening using the CRISPR/Cas9 knockout technique based on data mining across TCGA data sets and verified the candidate target in preclinical models and breast cancer high-throughput sequencing data sets. Results: We identified that CDK12, co-amplified with HER2 in a high frequency, is powerful to sensitise or resensitise HER2-positive breast cancer to anti-HER2 TKIs lapatinib, evidenced by patient-derived organoids in vitro and cell-derived xenograft or patient-derived xenograft  in vivo . Exploring mechanisms, we found that inhibition of CDK12 attenuated PI3K/AKT signal, which usually serves as an oncogenic driver and is reactivated when HER2-positive breast cancers develop resistance to lapatinib. Combining CDK12 inhibition exerted additional suppression on p-AKT activation induced by anti-HER2 TKIs lapatinib treatment. Clinically, via DNA sequencing data for tumour tissue and peripheral blood ctDNA, we found that HER2-positive breast cancer patients with CDK12 amplification responded more insensitively to anti-HER2 treatment than those without accompanying CDK12 amplification by harbouring a markedly shortened progression-free survival (PFS) (median PFS: 4.3 months versus 6.9 months; hazards ratio [HR] = 2.26 [95% confidence interval [CI] = 1.32–3.86]; P = 0.0028). Conclusions: Dual inhibition of HER2/CDK12 will prominently benefit the outcomes of patients with HER2-positive breast cancer by sensitising or resensitising the tumours to anti-HER2 TKIs treatment. Highlights: CRISPR/Cas9 knockout library screening identified CDK12 linking anti-HER2 TKIs resistance. CDK12 inhibition increased the efficacy of anti-HER2 tyrosine kinase inhibitors lapatinib. CDK12 suppression repressed activation of PI3K/AKT signalling pathway. HER2 + breast cancer patients with CDK12-amplification are resistant to HER2-targeted treatment.